Impact of Antiretroviral Therapy on Liver Fibrosis Among Human Immunodeficiency Virus-Infected Adults With and Without HBV Coinfection in Zambia. (4th February 2017) - Vinikoor, Michael J.; Sinkala, Edford; Chilengi, Roma; Mulenga, Lloyd B.; Chi, Benjamin H.; Zyambo, Zude; Hoffmann, Christopher J.; Saag, Michael S.; Davies, Mary-Ann; Egger, Matthias; Wandeler, Gilles; ,
Summary: Human immunodeficiency virus–infected Zambian adults had reduced liver stiffness after initiation of tenofovir-containing antiretroviral therapy, regardless of hepatitis B virus (HBV) coinfection. Despite good early virological and serological response to therapy, HBV coinfected patients had increased odds of significant fibrosis/cirrhosis at follow-up. Abstract: Background: We investigated changes in hepatic fibrosis, based on transient elastography (TE), among human immunodeficiency virus (HIV)–infected patients with and without hepatitis B virus (HBV) coinfection on antiretroviral therapy (ART) in Zambia. Methods: Patients' liver stiffness measurements (LSM; kiloPascals [kPa]) at ART initiation were categorized as no or minimal fibrosis (equivalent to Metavir F0–F1), significant fibrosis (F2–F3), and cirrhosis (F4). TE was repeated following 1 year of ART. Stratified by HBV coinfection status (hepatitis B surface antigen positive at baseline), we described LSM change and the proportion with an increase/decrease in fibrosis category. Using multivariable logistic regression, we assessed correlates of significant fibrosis/cirrhosis at 1 year on ART. Results: Among 463 patients analyzed (61 with HBV coinfection), median age was 35 years, 53.7% were women, and median baseline CD4+ count was 240 cells/mm 3 . Nearly all (97.6%) patients received tenofovir disoproxil fumarate–containing ART, in line with nationally recommended first-line treatment. The median LSM change was −0.70 kPa (95% confidence interval, −3.0 to +1.7) and was similar with and without HBV coinfection. Significant fibrosis/cirrhosis decreased in frequency from 14.0% to 6.7% ( P < .001). Increased age, male sex, and HBV coinfection predicted significant fibrosis/cirrhosis at 1 year (all P < .05). Conclusion: The percentage of HIV-infected Zambian adults with elevated liver stiffness suggestive of significant fibrosis/cirrhosis decreased following ART initiation—regardless of HBV status. This suggests that HIV infection plays a role in liver inflammation. HBV-coinfected patients were more likely to have significant fibrosis/cirrhosis at 1 year on ART. Clinical Trials Registration: NCT02060162.